A new reconfigurable intelligent-surface-assisted LoRa system - Zhang, Xiaoyu (2022)
Although LoRa modulation can achieve low-power and long-range transmission, its performance is significantly affected by fading channels. On the other hand, its low data rate limits the capacity. To mitigate these disadvantages, a new reconfigurable intelligent surface (RIS) assisted LoRa uplink system is proposed in this paper, where the reflection coefficients of the RIS are generated by utilizing an M-ary differential phase shift keying modulator. Moreover, a low-complexity non-coherent receiver is designed for the proposed system. The new system is able to inherit the non-coherent detection of the conventional LoRa system and also transmit additional information of log2M bits while reducing the impact of the fading channels. Furthermore, the bit-error-rate, symbol-error-rate and throughput expressions of the system are derived in closed form. Theoretical and simulated results show that the system has better performance than the conventional LoRa system and single-relay LoRa system.